T-Cell Assay after COVID-19 Vaccination Could Be a Useful Tool? A Pilot Study on Interferon-Gamma Release Assay in Healthcare Workers - Silva Seraceni; Elena Zocca; Tamara Emanuela Cervone; Flaminia Tomassetti; Isabella Polidori; Massimiliano Valisi; Francesco Broccolo; Graziella Calugi; Sergio Bernardini; Massimo Pieri (Diseases, 2022)
Background: SARS-CoV-2 T-cells are crucial for long-term protection against reinfection. The aim was to demonstrate the Interferon-gamma Release Assay (IGRA) test could be useful for vaccination monitoring. Methods: In a prospective cohort of 98 vaccinated healthcare workers for SARS-CoV-2, we selected 23 people in low-antibodies (Group 1, N = 8), high-antibodies (Group 2, N = 9), and negative control groups (Group 3, N = 6). SARS-CoV-2-specific humoral and cellular responses were analyzed at 8 months after two doses of Pfizer BioNTech, evaluating anti-RBD (Receptor Binding Domain) and RBD-ACE2 (Angiotensin Converting Enzyme-2) blocking antibodies in sera through a Chemiluminescence Immunoassay (CLIA) and T-cells through the IGRA test in heparinized plasma. Moreover, lymphocyte subtyping was executed by a flow cytometer. Statistical analysis was performed. Results: The data confirmed that RBD and RBD-ACE2 blocking ACE2 antibody levels of Group 1 were significantly lower than Group 2; p < 0.001. However, T-cells showed no significant difference between Group 1 and Group 2. Conclusions: This work suggests the need for new strategies for booster doses administration.